The impact of social relations on Job performance in government institutions (Raparin Journal of Humanities (RJH), 2023)
The aim of this study is to find out the effect of social relationships among employees of public institutions on the performance of their duties, as well as to present the level of social relationships of employees inside and outside the institutions.  Then, based on the data obtained from the survey of 270 units, and then analyzed the data with statistical tools, it was concluded that informal social relationships have an impact on the performance of employees.  There are also differences between men and women in the level of social relationships of employees outside the institutions.